Assessment of ehealth information seeking behavior of higher learning education students - Munassar, Fatimah Hasan Ali (Kulliyyah of Information and Communication, International Islamic University Malaysia, 2015)
The existence of internet has played a potential role in the process of information dissemination in the global context. The era of pervasive information regardless of the nature of information is clearly witnessed and no one can overlook its impact on our daily activities and issues. Due to the power of ICT in the field of health information sharing, it becomes so hard to control the explosion of health information over the internet and maintain its content; therefore student seeking information behavior particularly in the context of health-related information becomes the major issue highlighted by several researchers since students are the backbone of the community. Seeking any type of information is a basic activity performed by students resulting in raising the issue of how effectively and efficiency they search and apply the retrieved health-related information. This study has applied the Lily Model of eHealth literacy that consists of six skills of literacy to examine the level impact of these literacy skills on the level of eHealth search's efficacy of the students. Additionally, in this study internet barriers and online healthcare benefits have been measured and examine against eHealth search's efficacy. A Survey questionnaire has been selected as a data collection tool and distributed among university students who pursue their study in Malaysia. Descriptive analysis and Bootstrap method in Partial least square software (SmartPLS) are used to answer the study research questions. Factor analysis is conducted on internet barriers and eHealth benefits to detect the likelihood of reducing the number of variables which are dealt with. The study has unveiled the importance of certain literacy skills that must be present in the time of conducting a health-related search. It showed that health and information literacy are the core literacy skills that student should possess beside the computer literacy skill. On the other hand, Media literacy skill, scientific literacy skill and Traditional literacy skill were not significant barriers to higher education learning students. Internet barriers showed the unrelated relationship with the students' efficiency level of health-related search whilst eHealth benefits showed a strong positive relationship with eHealth search's efficacy. Internet barriers are being grouped in to two factors and eHealth benefits as well. Keywords: Information seeking behavior, Health informatics, eHealth Literacy, Internet and Health-related information, eHealth benefits